Pendekatan Sistem Dalam Peningkatan Kualitas Pembelajaran - Najah, Nadia; Fattah Nasution, Abdul; Mnr, Istiqomah; Fitria, Salsabila; Solehatun, Sri; Lubis, Zulfikar (Widya Balina, 2024)
Abstract. The systems approach is a holistic method used to improve the quality of learning by considering all interrelated elements in an educational ecosystem. This approach emphasizes the importance of synergy between various components, such as curriculum, educators, students, technology, learning environment, and education policy. With a systems approach, the learning process is not only focused on the transfer of knowledge, but also on the formation of critical skills, collaboration, and problem-solving in accordance with the demands of the globalization era. This study aims to analyze the application of a systems approach in improving the quality of learning at various levels of education. The methodology used involves library research studies. It was found that this approach was able to increase student participation, improve learning outcomes, and create an inclusive learning environment. However, the implementation of a systems approach requires consistent policy support, adequate resource allocation, and collaboration between stakeholders. This research emphasizes that a systems approach is not only relevant but also crucial in facing educational challenges in the digital era, making learning more adaptive, effective, and sustainable.